Racism, racial discrimination and child and youth health: a rapid evidence synthesis - Guo, Jun; Doery, Kate; Perry, Ryan; Jones, Roxanne; Priest, Naomi; Thurber, Katherine (My University, 2021)
This report focuses on Australian data collected in the last five years (2016–2020) and underscores the high prevalence of racial discrimination experienced by children and young people from Aboriginal and Torres Strait Islander backgrounds, and from some ethnic minoritised groups. It also focuses on what works in interventions to reduce the impacts of racism on health. Existing data is under-utilised and substantial data gaps remain. To inform the targeting of future action across policy, research and practice, investment is needed in the analysis of data already collected and to quantify and capture children and young people’s contemporary experiences of racial discrimination.
Keywords: Adolescents and youth; Disadvantage, adversity and resilience